The effects of manager’s strategic vision on innovation performance: A macro-level study - Lull, Juan Jose; Cervelló-Royo, Roberto; Galdon-Salvador, Jose-Luis (JOINETECH, 2025)
Knowledge management has strong importance in innovative processes, furthermore, it can be stated that competitive intelligence and knowledge generation systems for top managers have effect on business innovation. This article establishes a theoretical framework based on the Resourced-Based View (RBV) to analyze the role of top managers’ strategic vision in the success of innovation processes and to provide some empirical evidence of the value of business intelligence systems on the innovation performance in the organizations. Results show there is a strong relationship between top managers’ vision and innovation performance; moreover, from the relevance of the top managers’ vision derives the value of the business intelligence systems, which is the top managers’ main tool for learning and knowledge creation.
Keywords: innovation; knowledge management; business intelligence; strategic vision